Pelaksanaan Operan Jaga Perawat di Unit Rawat Inap: Studi Fenomenologi Deskriptif - Dina Mariana Larira; Ketut Rasmiati; Dewi Arwini Bugis (Faletehan Health Journal, 2022)
One of nurse professionalism can be reflected in the implementation of good communication in carrying out shift. Gaps in the implementation of nurse shift can interfere with the safety of hospitalized patients. The purpose of this study was to explore and understand in depth how the implementation of nurse shift in inpatient unit. This study used qualitative method. The data were collected by using triangulation methods, namely individual interviews with 3 key informants, focus group discussions with 4 nurses, and analyzing 10 documents related to the implementation of nurse shift, such as report books, register books, patient status and SOP of shift implementation. The number of samples until reaching data saturation was 7 informants and 10 related documents. The data found were then analyzed by using Colaizzi approach and resulted five themes, namely: (1) The process of shift implementation, (2) Benefits of shift implementation for nurses, (3) Nurses' understanding and expectations related to shift, (4) Barriers and consequences of shift ineffectiveness, (5) The support of the effectiveness of shift implementation. To conclude, nurse shift can be implemented effectively due to, one of the reasons, leader support in the form of directive mandatory to participate nurse shift.